A coplanar waveguide tapered slot antenna with beam switching capabilities - Delphine Abijuru; M. R. Hamid; N. Seman; M. Himdi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
A wideband tapered slot antenna (TSA) with three radiating elements for beam switching purpose is proposed in this study. The integrated radiating taper slots in assistance with metal strips acting as switches provided the proposed design with the capability of switching its beam into three different directions while maintaining the antenna performance stable. To validate the accuracy of the proposed design, the prototype was fabricated and measurements were conducted in terms of reflection coefficient (S11), radiation pattern and realized gain towards the three different operating modes. By sequentially, activating the switches, the antenna main beam rotated 90º in the XY coordinates. A realized gain ranging from 4.3 to 6.4 dBi and a wide operating bandwidth (|S11| ≤-10dB) from 3.3 GHz to 5 GHz  were observed throughout the antenna performance in simulation as well as in experiment. With the covered bands, the proposed antenna can be suitable for Sub -6GHz wireless communications systems. Improvements of Trapezoid Antenna Gain using Artificial Magnetic Conductor and Frequency Selective Surface.